PHENOMENOLOGY OF CHOGHA ZANBI¯L ZIGGURAT - Behrouz Afkhami (Journal of Ancient History and Archaeology)
Phenomenology in archeology is an interpretive method that addresses the existential philosophy of memorial sites as well as rational and better understanding, with regard to their manifestation. In this paper, phenomenology, as a methodology, examines the most prominent site of the historical period of the Middle Elam, which has a world-class value. Chogha Zanbı¯l gave the people of Elam a fundamental sense of rootedness. The placement of the Ziggurat at the central point, the core and the heart of Dur Untash, also manifests the significance of religion in the Elamite era. The Ziggurat affected the personal and collective circumstances of the people of Elam and gave objectivity to their religious beliefs. This objectivity met the most basic needs of the Middle Elam's people, and this meaningful experience was the basis for his "being". This essay studies Chogha Zanbı¯l Ziggurat using qualitative and phenomenological interpretation methodology, and concludes that the purpose of Untash Napirasha in making this great work was the permanent transfer of the religious center from Mesopotamia to Elam, the subjugation of the people and the sustainable propaganda for religious-political ideologies.